Integrating instructional technologies in teaching: The case of Malkerns primary schools, Eswatini (International Journal of Scientific Research and Management (IJSRM), 2022)
Abstract: The purpose of the study was to establish how educators integrate instructional technologies during teaching in Malkerns primary schools, located in the Manzini region of the Kingdom of Eswatini. The main focus of this study was on the training and support that educators receive towards the integration of instructional technologies in teaching as well as strategies to be put in place in order to curb the challenges faced. The study employed a qualitative approach and a descriptive research design in which face-to-face interviews and focus group discussion were used to collect data. Purposive sampling was used to select the five head teachers, ten educators as change leaders and two computer educators from five selected schools in the Malkerns cluster. The data was analysed using thematic analysis. The main conclusions of the study were that the availability of instructional technologies in schools does not mean that they are integrated during the teaching process. The study also concluded that educators have inadequate technological training and inadequate support which hinder effective instructional technologies integration in teaching. It is recommended that appropriate training programmes for educators, establishment of fully-fledged computer laboratories and an Information and Communication Technology (ICT) policy to support instructional technologies should be put in place to ensure successful integration of instructional technologies in teaching.